Saratuspersen Band dan Pengembangan OPK Seni di Kota Bandung - Zulkarnaen, Rudy; soni reffali (Paraguna, 2025)
Since the invention of information and communication technology, especially what is known today as the "internet" in the early 90s, the world has experienced significant changes in terms of interconnectedness. Not only between individuals, but further involving communication between regions, countries, and especially communication between cultures that are more open, including the dimensions of art, especially the world of tradisional arts that is affected. In particular, according to Van Dijk, social media, apart from being an industrial media in its development today, before that the media platform had a dimension to the existence of users or users, which provided space for users to do activities and collaborate, or even just express themselves. (in Dilaovita, 2016) In relation to culture, especially tradisional and performing art, the presence of social media, in this case Tik-tok, has presented a new performance ecosystem. Traditionally, performing arts, whatever their form, from traditional to contemporary, always require a stage in the material sense, but after the presence of Tik-toksocial media, everyone can express themselves anytime, anywhere, with appreciators, audiences who are not limited by time and place. The study in this paper specifically focuses on the discourse of the digital stage by using a digital research approach in seeing new opportunities for performance in the digital era.